Deoxynivalenol in chicken feed alters the vaccinal immune response and clinical biochemical serum parameters but not the intestinal and carcass characteristics. Issue 1 (21st April 2015) - Ghareeb, K.; Awad, W. A.; Zebeli, Q.; Böhm, J.
Summary: This study was conducted to investigate the impacts of deoxynivalenol (DON) feeding either alone or in combination with a microbial feed additive (MFA) on the immune response to a viral vaccine and serum clinical chemical parameters. Forty 1‐day‐old boiler chicks were weighed and randomly divided into four groups, 10 birds in each group: (i) control group fed with basal diet; (ii) DON group fed with basal diet artificially contaminated with 10 mg DON/kg feed; (iii) DON + MFA group fed with basal diet contaminated with 10 mg DON/kg feed and supplemented with 2.5 kg of MFA/ton feed; and (iv) MFA group fed with basal diet supplemented with 2.5 kg of MFA/ton feed. At 35 days of age, birds were slaughtered and blood was collected for investigating the antibody titre against infectious bronchitis virus (IBV) and clinical chemical parameters. The results showed that DON reduced (p = 0.032) the titre against IBV, decreased (p = 0.005) the level of alanine transaminase (ALT) (4.2 ± 0.5 U/l) compared with control birds (6.4 ± 0.5 U/l), increased (p = 0.002) the serum cholesterol concentration (144 ± 6 mg/dl) compared with their control counterparts (123 ± 5 mg/dl) and increased (p = 0.074) the amount of circulating triglycerides (62.25 ± 7.50 mg/dl) compared with controls (39.55 ± 4.74). These results indicate that dietary DON altered the humoral immune response to viral vaccine and affected the serum clinical biochemistry. However, DON in combination with MFA did not affect serum IBV titre. Taken together, DON in the feed of broilers produced an impairment of the success of IBV vaccine and affected the health of birds.